2011
DOI: 10.5897/ajb11.2075
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrient uptake of maize plants as affected by elemental sulfur and nitrogen fertilizer in sandy calcareous soil

Abstract: ) with application of S 0 at rates of 5 and 10 t ha -1 combined with N fertilizer in both Al Zaid and Al Semaih soils, respectively. Soil acidity improved by decreasing soil pH (1.41 to1.52 unit) with application of S 0 at the rate of 10 t ha -1 combined with N fertilizer. Addition of S 0 at the rate of 5 t ha -1 combined with N fertilizer recorded superior total dry matter (TDM) and maximum uptake of all nutrients in both soils. Total dry matter accumulation and nutrient uptake had positive correlation, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…Moreover, the higher the dose of sulfur introduced into the soils, the lower the determined pH of those soils. Similar results were presented by Yang et al [32], Rahman et al [33], Skwierawska et al [34] and Karimizarchi et al [35]. Matos Castañon et al [36] concluded that soil pH was decreased linearly with increasing elemental sulfur doses.…”
Section: Soil Ph Kclsupporting
confidence: 79%
“…Moreover, the higher the dose of sulfur introduced into the soils, the lower the determined pH of those soils. Similar results were presented by Yang et al [32], Rahman et al [33], Skwierawska et al [34] and Karimizarchi et al [35]. Matos Castañon et al [36] concluded that soil pH was decreased linearly with increasing elemental sulfur doses.…”
Section: Soil Ph Kclsupporting
confidence: 79%
“…The highest dry weight per plant was recorded in T4 (155.5gm), followed by T3 (145gm), T5 (143.1gm), and T2 (129.5gm), while the control group had the lowest dry weight per plant of T1 (117.8gm). Pandey et al,2008 andRahman et al,2011 reported that application of elemental sulphur significantly increase the dry weight [32,33]. Similar result were reported by Kumar et al 2014 [34].…”
Section: Height Of Cobsupporting
confidence: 55%
“…Srinivasarao et al, (2010) [53] concluded that plant height and dry matter production was maximum with application of sulphur at 20 kg ha -1 than control. Rahman et al, (2011) [36] divulged that dry matter production increased with application of elemental sulphur 5 t ha -1 from his study. Jeet et al, (2012) [18] observed a significant increase in plant height, number of green leaves plant -1 , LAI and dry matter plant -1 with sulphur application at 45 kg S ha -1 in maize.…”
Section: Introductionmentioning
confidence: 85%